A Catalyst-Free One-Pot Protocol for the Construction of Substituted Isoindolinones under Sustainable Conditions - Sashidhara, Koneni V.; Singh, L. Ravithej; Palnati, Gopala Reddy; Avula, Srinivasa Rao; Kant, Ruchir (Synlett, 2016)
An operationally simple, one-pot, catalyst-free method was developed for the synthesis of pharmaceutically important substituted isoindolinones by a three-component reaction of 2-formylbenzoic acid, a primary amine, and a 1,3-dione in ethanol under dielectric heating.
Keywords: isoindolinones; medicinal chemistry; multicomponent reaction; formylbenzoic acid; amines; diones